THE IMPACT OF FOOD AND WINE HARMONIZATION ON THE EXPERIENCE AND FUTURE INTENTIONS OF THE GUEST - Ćirić, Ivana Bojan; Tešanović, Dragan; Vujasinović, Vesna; Ćirić, Miloš (Economics of Agriculture, 2022)
In order to find out whether the guests like to pair food and wine, a research was conducted on the basis of experiences on harmonization of food and wine in Belgrade. The aim of the research was to determine whether sociodemographic characteristics influence the factors of gastro-oenological offer. In order to contribute to the development of catering facilities and their offerings, one of the main research factors was the factor of future intention to revisit and verbally promote the restaurant. A structured field survey questionnaire was conducted on a sample of 226 guests of catering facilities on the territory of Belgrade. The generated data was processed by the SPSS software package, including MANOVA analyzes and descriptive statistics. The obtained results show that sociodemographic characteristics influence the selection of gastro-oenological offer and experience related to the harmonization of food and wine and future intentions.